Efektivitas Penggunaan Internet dalam Mengakses Situs Keagamaan terhadap Hasil Belajar Pendidikan Agama Islam Siswa Kelas XI di SMA Negeri 2 Kaur (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2025)
This study aims to determine the effectiveness of internet use, particularly religious websites, on students' academic achievement. The development of information technology has encouraged students to access various online learning resources, including those related to religion. Religious websites such as [examples: Islamweb, Katolisitas, HinduToday, etc. serve as references for deepening religious subject matter as well as enriching students’ spiritual understanding. The research method used is quantitative with a survey approach involving 100 junior and senior high school students who actively access religious websites. The results indicate a significant positive correlation between the frequency of accessing religious websites and improved academic performance in religious studies. In addition, students who regularly utilize online religious content tend to have better religious attitudes and a deeper understanding of the material. These findings suggest that the internet, when used appropriately, can be an effective learning tool in supporting academic achievement, especially in religious education.
Keywords: internet; religious websites; academic achievement; religious education; educational technology